(untitled) (Journal of Engineering, 2016)
This research is concerned to investigate the behavior of reinforced concrete (RC) deep beams strengthened with carbon fiber reinforced polymer (CFRP) strips. The experimental part of this research is carried out by testing seven RC deep beams having the same dimensions and steel reinforcement which have been divided into two groups according to the strengthening schemes. Group one was consisted of three deep beams strengthened with vertical U-wrapped CFRP strips. While, Group two was consisted of three deep beams strengthened with inclined CFRP strips oriented by 45o with the longitudinal axis of the beam. The remaining beam is kept unstrengthening as a reference beam. For each group, the variable considered was the center to center spacing between strips (orthogonal spacing) which are (100 mm, 125 mm and 150 mm). Based on the experimental results it is found that the strengthening deep beams with CFRP strips by the two strengthening schemes, the mid-span deflection was decreased and both first cracking and ultimate loads capacities were increased compared to reference deep beam. For beams having the same spacing between strips, the enhancement occurred by using vertical U- wrapped scheme was somewhat better than using inclined scheme but it needs to use additional numbers of CFRP strips. The percentages increase in first cracking and ultimate loads were (50.0%, 46.0% and 20.5%) and (14.6%, 13.3% and 12.2%) respectively for beams strengthened with vertical U-wrapped scheme. While these percentages were changed to (36.5%, 18.0% and 12.5%) and (12.5%, 10.4% and 8.6%) for beams strengthened with inclined scheme. These results were obtained for center to center spacing between strips of (100 mm, 125 mm and 150 mm) respectively. The analytical part of this research was also adopted using the ACI 440 Code provisions to calculate the additional shear resistance carried by the CFRP strips. Good agreement was obtained between the experimental and analytical results.